2019
DOI: 10.2174/1573405614666180815115756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between 3D Echocardiography and Cardiac Magnetic Resonance Imaging (CMRI) in the Measurement of Left Ventricular Volumes and Ejection Fraction

Abstract: Background: Echocardiography and Cardiac Magnetic Resonance Imaging (CMRI) are two noninvasive techniques for the evaluation of cardiac function for patients with coronary artery diseases. Although echocardiography is the commonly used technique in clinical practice for the assessment of cardiac function, the measurement of LV volumes and left ventricular ejection fraction (LVEF) by the use of this technique is still influenced by several factors inherent to the protocol acquisition, which may affect the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…However, a significant proportion of patients with myocardial infarction still miss the optimal time to open the vessel for various reasons and opt for elective PCI [18]. Elective PCI delays reperfusion time, and some myocardium undergoes irreversible necrosis, which is not conducive to stopping the progression of ventricular remodeling [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant proportion of patients with myocardial infarction still miss the optimal time to open the vessel for various reasons and opt for elective PCI [18]. Elective PCI delays reperfusion time, and some myocardium undergoes irreversible necrosis, which is not conducive to stopping the progression of ventricular remodeling [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, 3D echo results correlate with CMR because of absence of geometric assumptions. 16 The literature showed similar heterogeneity in the results of echo and SPECT scan. Rawala et al 17 reported significant discordance (r=0.43) in LVEF between SPECT scan and echo in patients who had LVEF between 25% and 50% with a mean±SD LVEF of 46%± 11.3% and 42%±10.3%, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Estimation of LVEF using the Simpson biplane method is dependent on the image plane and other geometric assumptions [ 22 ], whereas 3D measurement of LVEF offers better reproducibility and less inter- and intra-observer variability. In addition, 3D LVEF appears to be a better predictor of adverse events than 2D LVEF and has a strong correlation with LVEF measured by CMR [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%